IMPLEMENTASI KEBIJAKAN PELINDUNGAN DATA PRIBADI PENGGUNA KARTU SIM PRABAYAR TELKOMSEL SIMPATI DI DAERAH KHUSUS IBUKOTA JAKARTA - Kintan Aqilla; Lusia Astrika (Journal of Politic and Government Studies, 2026)
The rapid advancement of digital technology has made personal data an inseparable part of modern life and a strategic asset in the provision of telecommunications services. However, this massive digitalization has also introduced new vulnerabilities, particularly in the use of prepaid SIM cards which require the submission of identity data as a prerequisite for service access. Although the Government of Indonesia has enacted Law Number 27 of 2022 concerning Personal Data Protection as the primary legal instrument, in practice, there remains a gap between regulatory provisions and field implementation. Based on these conditions, this research aims to analyze the implementation of personal data protection policies in the management of Telkomsel prepaid SIM card user data in the Special Capital Region of Jakarta. This research employs a qualitative approach with a descriptive method, where the analysis is conducted by grounding arguments in public policy implementation theory and the theory of the right to privacy. Through in-depth interviews, observations, and documentation involving regulators, cellular operators, and users, it was found that the policy implementation has proceeded administratively at the corporate level through the fulfillment of technical standards. However, substantively, such protection has not been fully felt by users, characterized by low digital literacy and a lack of real individual control over the personal data submitted. The discrepancy between the implemented policies and the public's perception of security indicates that without strong oversight and massive education, personal data protection policies in the telecommunications sector have not been fully effective in providing security guarantees for users' personal data.